Molecular investigation of feline coronavirus (FCoV) in local pet cats - Liew, Wuan Hoong (2017)
Feline coronavirus (FCoV) infection is very common in cat population. FCoV is further classified into two biotypes namely feline enteric coronavirus (FECV) and mutated feline infectious peritonitis virus (FIPV), in which FIPV causes a fatal immune complex disease by changing the tropism from enterocytes to monocytes. Previous studieson molecular detection of FCoVin cats were carried out in catteries but there is limited study on investigation of the presence of FCoV antigen in local pet cats. By considering this fact, this study aims to detect FCoV antigen via RT-PCR assay in local pet cats and to compare the similarity of the identified FCoV strain with previous related virus by phylogenetic analysis. By using convenience sampling, rectal swabs and buffy coat were collected from 16 clinically ill pet cats and 5 healthy pet cats. Viral RNA was extracted and subjected to one-step RT-PCR, targeting polymerase gene. Only 1 out of 21fecal samples was positive for FCoV and none for buffy coat. Phylogenetic analysis revealed that the identified positive sample was highly homologous, up to 95%, to aFCoV strain from Netherlands on partial sequence of polymerase gene. In conclusion, this study detected FCoV antigen in local pet cats and negative detection could not completely rule out the possibilities of FCoV infection due to the complexity of the virus diagnosis that require multiple series of analysis.